Review: Potensi Obat Tanaman Moringa oleifera - Dede Rival Novian (Wellness And Healthy Magazine, 2022)
The Moringa plant (Moringa Oleifera) is a small tree with a height of about 5 to 10 m. Moringa plants can be cultivated in all regions in Indonesia because they are suitable for all tropical climates in Indonesia. Every part of the Moringa plant can be used for nutrition and/or medicine. Apart from being a good source of protein, Moringa contains vitamins, oils, fatty acids, minerals and various phenolics, Moringa is also reported as an antimicrobial, anthelmintic, anti-inflammatory, anti-asthmatic, analgesic, antipyretic, antihypertensive, diuretic, cholesterol-lowering, antidiabetic, antioxidant, hepatoprotective, antitumor, antifertility, antispasmodic, antiulcer, cardiac stimulant and improve blood circulation. Its various pharmaceutical effects are identified as therapeutic drugs for various ailments in traditional medicine systems. This study provides a brief overview of the medicinal potential of the Moringa plant and its future as a component of modern medical systems. This study concludes that the Moringa plant requires a more comprehensive follow-up assessment to prove its ability in more modern medicine. Abstrak: Tanaman Kelor (Moringa oleifera) adalah pohon berukuran kecil dengan tinggi sekitar 5 sampai 10 m. Tanaman kelor dapat dibudidayakan di seluruh wilayah di Indonesia karena cocok dengan semua iklim trpis di Indonesia. Setiap bagian dari tanaman kelor dapat digunakan untuk nutrisi dan/atau obat. Selain sebagai sumber protein yang baik, kelor memiliki kandungan vitamin, minyak, asam lemak, mineral dan berbagai fenolik, kelor juga dilaporkan sebagai antimikroba, antihelmintik, anti-inflamasi, anti-asma, analgesic, antipiretik, Antihipertensi, diuretic, penurun kolesterol, antidiabtes, antioksidan, hepatoprotektif, antitumor, antifertilitas, antispasmodic, antiulkus, Stimulan jantung dan memperlancar peredaran darah. Berbagai efek farmasinya diidentifikasi sebagai obat terapeutik untuk berbagai penyakit dalam sistem pengobatan tradisional. Kajian ini memberikan gambaran singkat tentang obat-obatan potensi tanaman kelor dan masa depannya sebagai komponen sistem pengobatan modern. Studi ini menyimpulkan bahwa tanaman kelor membutuhkan penilaian lanjutan yang lebih komperhensif untuk membuktikan kemampuanya dalam pengobatan yang lebih modern.